Strong metal oxide-support interaction in MoO₂/N-doped MCNTs heterostructure for boosting lithium storage performance - Wang, Zhicheng (2023)
The low-rate capability and fast capacity decaying of the molybdenum dioxide anode material have been a bottleneck for lithium-ion batteries (LIBs) due to low carrier transport, drastic volume expansion and inferior reversibility. Furthermore, the lithium-storage mechanism is still controversial at present. Herein, we fabricate a new kind of MoO2 nanoparticles with nitrogen-doped multiwalled carbon nanotubes (MoO2/N-MCNTs) as anode for LIBs. The strong chemical bonding (MoOC) endows MoO2/N-MCNTs a strong metal oxide-support interaction (SMSI), rendering electron/ion transfer and facilitate significant Li+ intercalation pseudocapacitance, which is evidenced by both theoretical computation and detailed experiments. Thus, the MoO2/N-MCNTs exhibits high-rate performance (523.7 mAh/g at 3000 mA g-1) and long durability (507.8 mAh/g at 1000 mA g-1 after 500 cycles). Furthermore, pouch-type full cell composed of MoO2/N-MCNTs anodes and commercial LiNi0.6Co0.2Mn0.2O2 (NCM622) cathodes demonstrate impressive rate performance and cyclic life, which displays an unparalleled energy density of 553.0 Wh kg-1. Ex-situ X-ray absorption spectroscopy (XAS) indicates the enhanced lithium-storage mechanism is originated from a partially irreversible phase transition from Li0.98MoO2 to Li2MoO4 via delithiation. This work not only provides fresh insights into the enhanced lithium-storage mechanism but also proposes new design principles toward efficient LIBs.